Assessing the diagnostic accuracy of CT perfusion: a systematic review - Thirugnanachandran, Tharani; Aitchison, Sean G.; Lim, Andy; Ding, Catherine; Ma, Henry; Phan, Thanh (Frontiers in Neurology, 2023)
Background and Purpose: Computed tomography perfusion (CTP) has successfully extended the time window for reperfusion therapies in ischemic stroke. However, the published perfusion parameters and thresholds vary between studies. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses of Diagnostic Test Accuracy Studies (PRISMA-DTA) guidelines we conducted a systematic review to investigate the accuracy of parameters and thresholds for identifying core and penumbra in adult stroke patients. Methods: We searched Medline, Embase, the Cochrane Library and reference lists of manuscripts up to April 2022 using the following terms such as “computed tomography perfusion”, “stroke”, “infarct” and “penumbra.” Studies were included if they reported perfusion thresholds and undertook co-registration of CTP to reference standard. Quality of studies was assessed using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool and Standards for Reporting of Diagnostic Accuracy (STARD) guidelines. Results: 24 studies were included. A meta-analysis could not be performed due to insufficient data and significant heterogeneity in study design. When reported, mean age was 70.2 years (SD+/-3.69) and median NIHSS on admission was 15 (IQR 13 -17). Perfusion parameter identified for core was relative cerebral blood flow (rCBF), with a median threshold of <30% (IQR 30%, 40%). However, later studies reported lower thresholds in the early time window with rapid reperfusion (median 25%, IQR 20%, 30%). 15 studies defined a single threshold for all brain regions irrespective of collaterals and grey and white matter. Conclusion: A single threshold and parameter may not always accurately differentiate penumbra from core and oligemia. Further refinement of parameters is needed in the current era of reperfusion therapy.